Strategi pembentukan identitas diri influencer generasi z melalui media sosial: Studi kasus akun @kakloraa - Jona, Bryan Mahendra Putra; Febriana, Poppy (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2025)
This research uses the @kakloraa account as a case study to analyse the self-identity formation strategy of an influencer from Generation Z. Social media now plays a significant role in the lives of this generation, influencing the way they form, manage and express their self-identity. The theory applied in this research is Self-Presentation Theory using the Self-Presentation Strategy indicators developed by Edward E. Jones and Thane S. Pittman in the book Impression Management Theory and Social Psychological Research edited by James T. Tedeschi, this theory examines individuals' efforts to control how others perceive them. This research adopts a descriptive qualitative approach to gain an in-depth understanding of the experiences, views and processes involved in individual identity formation. The research applied three different data collection methods, namely documentation, interviews and observation. The data analysis process includes the steps of data reduction, data presentation, and conclusion drawing. The result of this research is that Kak Lora uses ingratiation, self-promotion and exemplification presentation strategies. With the implementation of these three strategies, Kak Lora managed to build a positive self-identity, increase audience loyalty and expand her influence in the world of food vloggers Keywords: Social Media; Self-Identity; Influencer; Generation Z